4-(3,3-Dimethylperhydro-1,3-oxazolo[3,4-a]pyridin-1-yl)-2,8-bis(triflu oromethyl)quinoline - Wardell, J.L.; Wardell, S.M.S.V.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
An L-shaped conformation is found in the title molecule, C20H20F6N2O, the C-C-C-C torsion angle linking the two fused-ring systems being -92.80 (19)degrees. The oxazole ring adopts an envelope conformation [the N atom lies 0.579 (2) angstrom out of the plane defined by the remaining atoms], and the piperidine ring has a chair conformation. Supramolecular chains are found in the crystal structure that are sustained by C-H center dot center dot center dot pi and pi-pi [3.6089 (10) angstrom] interactions.